1988
DOI: 10.1080/07055900.1988.9649299
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of model and indirectly measured diffuse sky irradiances of tilted surfaces

Abstract: The estimation of diffuse (short-wave)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Harrison and Coombes [9] compared simulation results for angular positions of 30°, 60°, 90° for 10 variants of cloudiness degree and showed that Liu-Jordan isotropic model lead to an underestimation of radiation power density, while the anisotropic Klucher and Hay models cause overestimation by a small percentage. Kudish and Ianetz [10], using the same three mathematical models (Liu-Jordan, Klucher, Hay) for the geographical location 31°15' N, 34°47' E, demonstrated strong variability of tested models as a function of the season of the year, measurement time and location described primarily by latitude angle.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison and Coombes [9] compared simulation results for angular positions of 30°, 60°, 90° for 10 variants of cloudiness degree and showed that Liu-Jordan isotropic model lead to an underestimation of radiation power density, while the anisotropic Klucher and Hay models cause overestimation by a small percentage. Kudish and Ianetz [10], using the same three mathematical models (Liu-Jordan, Klucher, Hay) for the geographical location 31°15' N, 34°47' E, demonstrated strong variability of tested models as a function of the season of the year, measurement time and location described primarily by latitude angle.…”
Section: Introductionmentioning
confidence: 99%